Environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium battery and preparation method thereof
By using modified silicon nitride as a thermal filler in polyurethane thermally conductive structural adhesive and using specific group distribution ratios and process steps, an environmentally friendly polyurethane thermally conductive structural adhesive was prepared, which solved the problem that existing adhesives could not meet the thermal conductivity and bonding properties at the same time, and achieved efficient thermal management and moisture-heat resistance.
Patent Information
- Application Number
- CN202411692812.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-01
AI Technical Summary
The existing polyurethane thermal structural adhesives cannot meet the requirements in terms of adhesive performance, flame retardant, insulation, thermal conductivity and moisture and heat resistance, and it is difficult to meet the needs of high discharge rate lithium batteries.
Modified silicon nitride is used as the thermal filler, and through specific component distribution ratios and process steps, an environmentally friendly polyurethane thermally conductive structural adhesive is prepared, including the mixing of components A and components B to ensure high thermal conductivity, good adhesive properties and moisture and heat-resistant aging of the adhesive.
It has achieved high thermal conductivity, excellent adhesive properties, good flame retardancy, insulation and moisture-heat aging resistance of polyurethane thermally conductive structural adhesives for energy storage lithium batteries, and met the needs of high discharge rate lithium batteries.
Smart Images

Figure BDA0005151412680000171 
Figure BDA0005151412680000181
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives for energy storage lithium batteries, in particular to an environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries and a preparation method thereof. Background Art
[0002] At present, the new energy vehicle market is developing rapidly, and the demand for new energy power batteries is also increasing. The demand for the continuous research and development of higher-rate charge and discharge lithium batteries is also growing. High-rate charge and discharge can not only meet people's high requirements for new energy mileage, but also achieve the sustainable development of the new energy vehicle industry. However, the existing higher-rate lithium batteries will generate a lot of heat during use. If the heat is not dissipated in time, the temperature of the battery will continue to rise, which will seriously affect the safety performance and service life of the battery. Lithium-ion batteries generate heat during the charging and discharging process. In order to transfer the heat generated by the battery to the cooling system of the battery pack, thermal conductive adhesive materials are required. The heat generated by the battery cell when working is exported to the external heat dissipation components to achieve some functions of thermal management. As an important part of the battery manufacturing process, the use of adhesives directly determines the structural stability and safety of the battery.
[0003] The structural adhesive for energy storage lithium batteries needs to reliably connect and fix the battery cell and the battery shell, so there are high requirements for its bonding performance, flame retardancy, insulation, moisture and heat aging resistance, and thermal conductivity. The current polyurethane thermal conductive structural adhesive cannot meet the requirements in terms of bonding performance, flame retardancy, insulation, thermal conductivity, and moisture and heat aging resistance at the same time.
[0004] Therefore, there is an urgent need to develop a polyurethane structural adhesive that has both excellent bonding performance and high thermal conductivity. Summary of the invention
[0005] To solve the above problems, the purpose of the present invention is to provide an environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries and a preparation method thereof.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] An environmentally friendly polyurethane thermally conductive structural adhesive for energy storage lithium batteries, wherein the environmentally friendly polyurethane thermally conductive structural adhesive for energy storage lithium batteries uses modified silicon nitride as a thermally conductive filler;
[0008] The modified silicon nitride is prepared according to the following steps:
[0009] Add silicon nitride to a potassium hydroxide aqueous solution, heat to 115-125°C for reaction for 40-50 hours under stirring, cool to 20-30°C, filter, wash with deionized water until the pH value of the filtrate is 7-8, and vacuum dry the filtered powder to obtain Si3N4-OH powder;
[0010] Add Si3N4-OH powder to silane coupling agent KH560-ethanol solution, stir and mix for 2 to 4 hours, centrifuge, wash the solid powder with ethanol, and vacuum dry to obtain modified silicon nitride;
[0011] The mass ratio of silicon nitride, potassium hydroxide aqueous solution, and silane coupling agent KH560-ethanol solution is 1:3-4:3-4;
[0012] The mass concentration of the potassium hydroxide aqueous solution is 3-7 mol / L;
[0013] The mass concentration of the silane coupling agent KH560-ethanol solution is 0.8-1.2%.
[0014] Preferably, the environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium battery is obtained by mixing component A and component B in a volume ratio of 1:1; the component A is composed of the following raw materials in parts by weight: 7 to 25 parts of a first polyether polyol, 1 to 15 parts of bisphenol A modified polyether polyol, 1 to 10 parts of modified castor oil, 0.5 to 3.5 parts of a chain extender, 0.2 to 2 parts of a first defoamer, 8 to 30 parts of a first flame retardant, 30 to 75 parts of modified silicon nitride, and an antioxidant. 0.2-2.5 parts, 0.05-1.5 parts of catalyst and 0.003-0.05 parts of first wetting and dispersing agent; the B component is composed of the following raw materials in parts by weight: 5-25 parts of silane-modified polyurethane polymer, 7-35 parts of second polyisocyanate, 0.5-2.5 parts of dewatering agent, 0.2-2 parts of second defoaming agent, 8-30 parts of second flame retardant, 30-70 parts of modified silicon nitride and 0.003-0.05 parts of second wetting and dispersing agent;
[0015] The first polyether polyol is a difunctional polyether polyol having a molecular weight of 400 to 2000;
[0016] The silane-modified polyurethane polymer is an isocyanate-terminated polymer terminated by a silane coupling agent, and the silane coupling agent is one or two of Dynasylan 1146, VOK-225, and VOK-Y-15744.
[0017] Preferably, the silane-modified polyurethane polymer is obtained according to the following steps:
[0018] Under stirring, adding the second polyether polyol to a reactor with nitrogen protection, heating to above 120° C., vacuum dehydrating to a water content of less than 500 ppm, stopping heating, cooling to 40-50° C., adding the first polyisocyanate, heating to 75-83° C., reacting for 3-4.5 hours, sampling to detect NCO%, when the NCO% content is 3.7-8.5%, stopping heating to obtain a terminal isocyanate polymer, cooling to 40-50° C., adding a silane coupling agent to react for 1-1.5 hours, cooling to 20-30° C. to stop the reaction, and obtaining a silane-modified polyurethane polymer;
[0019] The mass ratio of the second polyether polyol, the first polyisocyanate and the silane coupling agent is 100:26.3-78.0:10.2-61.5;
[0020] The second polyether polyol is a difunctional polyether polyol having a molecular weight of 700 to 2000;
[0021] The first polyisocyanate is one or two of L-lysine diisocyanate, MDI-50, dimethylenebenzene diisocyanate, and diphenylmethane diisocyanate;
[0022] The silane coupling agent is one or two of Dynasylan 1146, VOK-225 and VOK-Y-15744.
[0023] Preferably, the silane coupling agent is added to react for 1 to 1.5 hours, and when the NCO% content is 1.8 to 4.3%, the temperature is lowered to 20 to 30° C. to stop the reaction and obtain a silane-modified polyurethane polymer.
[0024] Preferably, the bisphenol A modified polyether polyol is one or two of HP-2000, HP-2280, HMP-604B, and ST-280;
[0025] The modified castor oil is one or two of SY770, HY-1002 and X150;
[0026] The first defoamer and the second defoamer are one or two of Defom 6800, BYK-A535, DF-8205, and DF-879D;
[0027] The first flame retardant and the second flame retardant are one or two of calcium sulfate inorganic fiber powder, zinc borate, and triphenyl phosphate;
[0028] The antioxidant is one or two of Irganox1135, SONOX168, SONOX1076, and Irganox B215;
[0029] The first wetting and dispersing agent and the second wetting and dispersing agent are one or two of DISPERBYK-145, Disponer 910, and HY5010;
[0030] The second polyisocyanate is one or two of modified isocyanate MDI, liquefied MDI, MDI-50, dimethylbenzene diisocyanate, and dicyclohexylmethane diisocyanate;
[0031] The dewatering agent is p-toluenesulfonyl isocyanate.
[0032] Preferably, the chain extender is one or two of propylene glycol, dipropylene glycol, 1,4-butanediol, and ethylene glycol.
[0033] Preferably, the catalyst is one or two of dibutyltin dilaurate, pentamethyldiethylenetriamine, dimorpholine diethyl ether, and triethylenediamine.
[0034] The present invention also includes a method for preparing an environmentally friendly polyurethane thermal conductive structural adhesive for an energy storage lithium battery, comprising the following steps:
[0035] ① Preparation of component A: by weight, add 7-25 parts of the first polyether polyol, 1-15 parts of bisphenol A modified polyether polyol, 1-10 parts of modified castor oil, 0.5-3.5 parts of chain extender, 8-30 parts of the first flame retardant, and 30-75 parts of modified silicon nitride into a reactor with nitrogen protection, heat to 120-130° C. under stirring, vacuum dry and dehydrate for 1.5-2.5 hours, cool to 30-40° C., add 0.2-2 parts of the first defoamer, 0.2-2.5 parts of the antioxidant, 0.003-0.05 parts of the first wetting and dispersing agent, and 0.05-1.5 parts of the catalyst, mix for 30-40 minutes, and then discharge to obtain component A;
[0036] The first polyether polyol is a difunctional polyether polyol having a molecular weight of 400 to 2000;
[0037] ② Preparation of component B: 5-25 parts of silane-modified polyurethane polymer, 7-35 parts of the second polyisocyanate, 8-30 parts of the second flame retardant, 30-70 parts of modified silicon nitride, 0.5-2.5 parts of dewatering agent, 0.2-2 parts of the second defoaming agent and 0.003-0.05 parts of the second wetting and dispersing agent were stirred and mixed for 30-40 minutes, and the mixture was discharged to obtain component B;
[0038] The silane-modified polyurethane polymer is an isocyanate-terminated polymer terminated by a silane coupling agent, and the silane coupling agent is one or two of Dynasylan 1146, VOK-225, and VOK-Y-15744;
[0039] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a volume ratio of 1:1 to obtain an environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries.
[0040] Compared with the prior art, the present invention has the following advantages:
[0041] The environmentally friendly polyurethane thermally conductive structural adhesive for energy storage lithium batteries of the present invention has good bonding performance, good thermal conductivity, flame retardancy, resistance to moisture and heat aging and electrical insulation, can meet the requirements of lithium batteries with high discharge rates, can be used for thermal insulation and sealing bonding of lightweight and ultra-strong structures of various electrical and mechanical systems, and is particularly suitable for structural bonding and thermally conductive structural bonding in the assembly process of energy storage lithium batteries, including bonding between battery cells, bonding between battery cells and end plates, bonding between battery cells and side plates, and bonding between battery cells and box bodies.
[0042] The environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries of the present invention adopts silane-modified silicon nitride added to polyurethane, which can greatly increase the thermal conductivity of the structural adhesive. The addition of silane coupling agent can increase the bonding performance of the structural adhesive, and can also be better compatible and dispersed with other components.
[0043] The environmentally friendly polyurethane heat-conductive structural adhesive for energy storage lithium battery of the present invention, on the one hand, uses polyether polyol in component A and bisphenol A modified polyether polyol and modified castor oil for compounding, and polyether polyol can provide excellent flexibility for the system; the benzene ring and carbon oxygen chain structure in the bisphenol A modified polyether polyol molecule can give the structural adhesive specific rigidity and toughness, and because of the high cohesive energy within the molecule, it has good high temperature resistance and hydrolysis resistance, can significantly improve the cohesive force and increase the bonding strength, so the prepared adhesive has good bonding performance and excellent resistance to moisture and heat. On the other hand, the synthesized terminal isocyanate polymer is partially capped by using a silane coupling agent oligomer to obtain a silane-modified polyurethane polymer, which contains a certain amount of -NCO groups and is compounded with monomeric isocyanate in component B for use. The siloxane structure in the modified polymer can react with the hydroxyl group on the substrate to enhance the adhesion of the structural adhesive on the substrate surface and effectively improve the adhesion of the adhesive product. The Si-O-Si cross-linked network layer in the silane coupling agent oligomer structure can effectively prevent the penetration of water molecules and has excellent hydrophobicity. It can effectively reduce the water absorption rate of the adhesive product and enhance the water resistance and moisture and heat resistance of the adhesive product. And because the modified polymer has good hydrophobicity, it does not need to add conventional ones into the system and can also have good storage stability. DETAILED DESCRIPTION
[0044] The purpose of the present invention is to provide an environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries and a preparation method thereof, which is achieved through the following technical solutions:
[0045] The following raw materials of the present invention were purchased from the following manufacturers and models:
[0046] The modified isocyanate MDI is Suprasec 3202, Suprasec 2496, and Suprasec 2020 produced by Huntsman Polyurethanes (China) Co., Ltd., and isocyanate PM 200 produced by Wanhua Chemical Group Co., Ltd.;
[0047] Dicyclohexylmethane diisocyanate is HMDI produced by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.;
[0048] Bisphenol A modified polyether polyol HP-2000 is the HP-2000 model produced by Shanghai Yinman Chemical Co., Ltd.; HP-2280 is the HP-2280 model produced by Shanghai Yinman Chemical Co., Ltd.; HMP-604B is the HMP-604B model produced by Zhejiang Huangma Technology Co., Ltd.; ST-280 is the ST-280 model produced by Nanjing Suterin New Material Technology Co., Ltd.;
[0049] Modified castor oil SY770 is the SY770 model produced by Shanghai Shuyu Chemical Co., Ltd.; HY-1002 is the HY-1002 model produced by Fucheng County Huanyu Co., Ltd.; X150 is the X150 model produced by Fucheng County Huanyu Co., Ltd.;
[0050] The calcium sulfate inorganic fiber powder is calcium sulfate inorganic fiber produced by Shanghai Yincheng New Material Technology Co., Ltd.;
[0051] The wetting and dispersing agent HY5010 is the HY5010 model produced by Fucheng County Huanyu Co., Ltd.;
[0052] Dicyclohexylmethane diisocyanate is HMDI produced by Hubei Wo Chemical Technology Co., Ltd.
[0053] The present invention is further described below in conjunction with specific embodiments.
[0054] Example 1
[0055] The modified silicon nitride is prepared, comprising the following steps:
[0056] ① Add 100 kg of silicon nitride to 300 kg of 3 mol / L potassium hydroxide aqueous solution, heat to 115 ° C for 50 hours under stirring, cool to 20 ° C, filter, wash with deionized water until the pH value of the filtrate is 7, and vacuum dry the filtered powder to obtain Si3N4-OH powder;
[0057] ② Add Si3N4-OH powder to 300kg of silane coupling agent KH560-ethanol solution, stir and mix for 2 hours, centrifuge, wash the solid powder with ethanol, and vacuum dry to obtain modified silicon nitride;
[0058] The mass concentration of the silane coupling agent KH560-ethanol solution is 0.8%.
[0059] Example 2
[0060] The modified silicon nitride is prepared, comprising the following steps:
[0061] ① Add 100 kg of silicon nitride to 400 kg of 7 mol / L potassium hydroxide aqueous solution, heat to 125 ° C for 40 hours under stirring, cool to 30 ° C, filter, wash with deionized water until the pH value of the filtrate is 8, and vacuum dry the filtered powder to obtain Si3N4-OH powder;
[0062] ② Add Si3N4-OH powder to 400kg of silane coupling agent KH560-ethanol solution, stir and mix for 4 hours, centrifuge, wash the solid powder with ethanol, and vacuum dry to obtain modified silicon nitride;
[0063] The mass concentration of the silane coupling agent KH560-ethanol solution is 1.2%.
[0064] Example 3
[0065] The modified silicon nitride is prepared, comprising the following steps:
[0066] ① Add 100 kg of silicon nitride to 350 kg of 5 mol / L potassium hydroxide aqueous solution, heat to 118 ° C for 42 hours under stirring, cool to 22 ° C, filter, wash with deionized water until the pH value of the filtrate is 7.2, and vacuum dry the filtered powder to obtain Si3N4-OH powder;
[0067] ② Add Si3N4-OH powder to 350kg of silane coupling agent KH560-ethanol solution, stir and mix for 2.5 hours, centrifuge, wash the solid powder with ethanol, and vacuum dry to obtain modified silicon nitride;
[0068] The mass ratio of silicon nitride, potassium hydroxide aqueous solution, and silane coupling agent KH560-ethanol solution is 1:3.5:3.5;
[0069] The mass concentration of the silane coupling agent KH560-ethanol solution is 1.0%.
[0070] Example 4
[0071] The modified silicon nitride is prepared, comprising the following steps:
[0072] ① Add 100 kg of silicon nitride to 320 kg of 6 mol / L potassium hydroxide aqueous solution, heat to 120 ° C for 45 hours under stirring, cool to 25 ° C, filter, wash with deionized water until the pH value of the filtrate is 7.5, and vacuum dry the filtered powder to obtain Si3N4-OH powder;
[0073] ② Add Si3N4-OH powder to 380kg of silane coupling agent KH560-ethanol solution, stir and mix for 3 hours, centrifuge, wash the solid powder with ethanol, and vacuum dry to obtain modified silicon nitride;
[0074] The mass concentration of the silane coupling agent KH560-ethanol solution is 1.1%.
[0075] The modified silicon nitride used in the following examples is the modified silicon nitride prepared in Examples 1 to 4.
[0076] Example 5
[0077] An environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries is obtained by mixing component A and component B in a volume ratio of 1:1; the component A is composed of the following raw materials: 7kg of a first polyether polyol, 1kg of bisphenol A modified polyether polyol HP-2000, 1kg of modified castor oil SY770, 0.5kg of a chain extender propylene glycol, 0.2kg of a defoamer Defom 6800, 8kg of a flame retardant calcium sulfate inorganic fiber powder, 30kg of modified silicon nitride, 0.2kg of an antioxidant Irganox1135, 0.05kg of a catalyst dibutyltin dilaurate, and 0.003kg of a wetting and dispersing agent DISPERBYK-145; the component B is composed of the following raw materials: 5kg of a silane modified polyurethane polymer, 5kg of Suprasec 32027kg, dehydrating agent p-toluenesulfonyl isocyanate 0.5kg, defoaming agent BYK-A5350.2kg, flame retardant zinc borate 8kg, modified silicon nitride 30kg and wetting and dispersing agent Disponer 9100.003kg;
[0078] The first polyether polyol is a difunctional polyether polyol with a molecular weight of 400;
[0079] The silane-modified polyurethane polymer is obtained by capping a terminal isocyanate polymer having an NCO% content of 3.7% with a silane coupling agent, and specifically comprises the following steps:
[0080] Under stirring, the second polyether polyol is added to a reactor with nitrogen protection, the temperature is raised to above 120° C., vacuum dehydration is performed until the moisture content is less than 500 ppm, heating is stopped, the temperature is lowered to 40° C., the first polyisocyanate is added, heated to 75° C. and reacted for 4.5 hours, sampling is performed to detect NCO%, when the NCO% content (m1) is 7.5%, heating is stopped to obtain a terminal isocyanate polymer, the temperature is lowered to 40° C., a silane coupling agent Dynasylan 1146 is added and reacted for 1.5 hours, when the NCO% content (m2) is 3.7%, the temperature is lowered to 35° C. and the reaction is stopped to obtain a silane-modified polyurethane polymer;
[0081] The mass ratio of the second polyether polyol, the first polyisocyanate and the silane coupling agent is 100:75.0:35.9;
[0082] The second polyether polyol is a difunctional polyether polyol with a molecular weight of 700;
[0083] The first polyisocyanate is MDI-50.
[0084] The effect of changing the type of the first polyisocyanate from MDI-50 to other types (methylenebenzene diisocyanate, diphenylmethane diisocyanate) in the preparation process of silane-modified polyurethane polymer on the NCO% content of the silane-modified polyurethane polymer.
[0085] Table 1
[0086] Selection of the first polyisocyanate <![CDATA[NCO% content (m1)]]> <![CDATA[NCO% content (m2)]]> L-Lysine diisocyanate 7.9% 3.9% Dimethylenephenyl diisocyanate 8.5% 4.3% Methylene diphenyl diisocyanate 7.5% 3.8%
[0087] It can be seen from the results in Table 1 that the NCO% content of the silane-modified polyurethane polymer of the present technology is related to the molecular weight of the second polyether polyol and the type of the first polyisocyanate, but the NCO% content of 1.8-4.3% can meet the requirements for the NCO% content in the silane-modified polyurethane polymer.
[0088] Example 6
[0089] An environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries is obtained by mixing component A and component B in a volume ratio of 1:1; the component A is composed of the following raw materials: 25 kg of a first polyether polyol, 15 kg of bisphenol A modified polyether polyol HP-2280, 210 kg of modified castor oil HY-100, 3.5 kg of a chain extender dipropylene glycol, 25 kg of a defoamer BYK-A53, 30 kg of a flame retardant zinc borate, 75 kg of modified silicon nitride, 2.5 kg of an antioxidant SONOX168, 1.5 kg of a catalyst pentamethyldiethylenetriamine and 0.05 kg of a wetting and dispersing agent Disponer 910; the component B is composed of the following raw materials: 25 kg of a silane modified polyurethane polymer, 25 kg of PMMA 20035kg, dehydrating agent p-toluenesulfonyl isocyanate 2.5kg, defoaming agent DF-82052kg, flame retardant triphenyl phosphate 30kg, modified silicon nitride 70kg and wetting dispersant HY50100.05kg;
[0090] The first polyether polyol is a difunctional polyether polyol with a molecular weight of 2000;
[0091] The silane-modified polyurethane polymer is obtained by capping a terminal isocyanate polymer having an NCO% content of 1.8% with a silane coupling agent, and specifically comprises the following steps:
[0092] Under stirring, adding the second polyether polyol to a reactor protected by nitrogen, heating to above 120° C., vacuum dehydrating to a moisture content of less than 500 ppm, stopping heating, cooling to 50° C., adding the first polyisocyanate, heating to 83° C., reacting for 3 hours, sampling to detect NCO%, when the NCO% content is 3.9%, stopping heating to obtain a terminal isocyanate polymer, cooling to 50° C., adding a silane coupling agent VOK-225, reacting for 1 hour, cooling to 30° C. to stop the reaction when the NCO% content is 1.9%, and obtaining a silane-modified polyurethane polymer;
[0093] The mass ratio of the second polyether polyol, the first polyisocyanate and the silane coupling agent is 100:19.5:19.5;
[0094] The second polyether polyol is a difunctional polyether polyol with a molecular weight of 2000;
[0095] The first polyisocyanate is dimethylenephenyl diisocyanate.
[0096] The effect of changing the type of the first polyisocyanate in the preparation process of silane-modified polyurethane polymer from methylenediisocyanate to other types (L-lysine diisocyanate, MDI-50, diphenylmethane diisocyanate) on the NCO% content of silane-modified polyurethane polymer.
[0097] Table 2
[0098] Selection of the first polyisocyanate <![CDATA[NCO% content (m1)]]> <![CDATA[NCO% content (m2)]]> L-Lysine diisocyanate 3.8% 1.9% MDI-50 3.6% 1.8% Methylene diphenyl diisocyanate 3.6% 1.8%
[0099] It can be seen from the results in Table 2 that the NCO% content of the silane-modified polyurethane polymer of the present technology is related to the molecular weight of the second polyether polyol and the type of the first polyisocyanate, but the NCO% content of 1.8-4.3% can meet the requirements for the NCO% content in the silane-modified polyurethane polymer.
[0100] Example 7
[0101] An environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries is obtained by mixing component A and component B in a volume ratio of 1:1; the component A is composed of the following raw materials: 10 kg of a first polyether polyol, 4 kg of bisphenol A modified polyether polyol HMP-604B, 2 kg of modified castor oil X150, 1 kg of a chain extender 1,4-butanediol, 0.5 kg of a defoamer DF-8205, 10 kg of a flame retardant triphenyl phosphate, 45 kg of modified silicon nitride, and an antioxidant Irganox. B2151kg, catalyst dimorpholine diethyl ether 0.1kg and wetting and dispersing agent DISPERBYK-1450.01kg; the B component is composed of the following raw materials: silane-modified polyurethane polymer 8kg, dimethylbenzene diisocyanate 10kg, dewatering agent p-toluenesulfonyl isocyanate 1kg, defoamer DF-82050.8kg, flame retardant triphenyl phosphate 10kg, modified silicon nitride 35kg and wetting and dispersing agent DISPERBYK-1450.02kg;
[0102] The first polyether polyol is a difunctional polyether polyol with a molecular weight of 600;
[0103] The silane-modified polyurethane polymer is obtained by capping a terminal isocyanate polymer having an NCO% content of 3.8% with a silane coupling agent, and specifically comprises the following steps:
[0104] Under stirring, adding the second polyether polyol to a reactor with nitrogen protection, heating to above 120° C., vacuum dehydrating to a water content of less than 500 ppm, stopping heating, cooling to 42° C., adding the first polyisocyanate, heating to 78° C., reacting for 3.5 hours, sampling to detect NCO%, when the NCO% content is 7.8%, stopping heating to obtain a terminal isocyanate polymer, cooling to 44° C., adding a silane coupling agent to react for 1 to 1.5 hours, cooling to 30° C. to stop the reaction when the NCO% content is 3.8%, and obtaining a silane-modified polyurethane polymer;
[0105] The mass ratio of the second polyether polyol, the first polyisocyanate and the silane coupling agent is 100:48.8:26.0;
[0106] The second polyether polyol is a difunctional polyether polyol with a molecular weight of 800;
[0107] The first polyisocyanate is dimethylenephenyl diisocyanate;
[0108] The silane coupling agent is VOK-Y-15744.
[0109] The effect of changing the type of the first polyisocyanate in the preparation process of silane-modified polyurethane polymer from methylenediisocyanate to other types (L-lysine diisocyanate, MDI-50, diphenylmethane diisocyanate) on the NCO% content of silane-modified polyurethane polymer.
[0110] Table 3
[0111] Selection of the first polyisocyanate <![CDATA[NCO% content (m1)]]> <![CDATA[NCO% content (m2)]]> L-Lysine diisocyanate 7.3% 3.6% MDI-50 7.0% 3.5% Methylene diphenyl diisocyanate 7.0% 3.5%
[0112] It can be seen from the results in Table 3 that the NCO% content of the silane-modified polyurethane polymer of the present technology is related to the molecular weight of the second polyether polyol and the type of the first polyisocyanate, but the NCO% content of 1.8-4.3% can meet the requirements for the NCO% content in the silane-modified polyurethane polymer.
[0113] Example 8
[0114] An environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries is obtained by mixing component A and component B in a volume ratio of 1:1; the component A is composed of the following raw materials: 15kg of a first polyether polyol, 7kg of bisphenol A modified polyether polyol HMP-604B, 4kg of modified castor oil SY770, 1.5kg of chain extender ethylene glycol, 1.5kg of defoamer DF-8205, 18kg of flame retardant calcium sulfate inorganic fiber powder, 45kg of modified silicon nitride, 1.8kg of antioxidant SONOX1076, 1kg of catalyst triethylenediamine and 1kg of wetting dispersant Disponer 9100.04kg; the B component is composed of the following raw materials: 15kg of silane-modified polyurethane polymer, 25kg of MDI-50, 1.8kg of dewatering agent p-toluenesulfonyl isocyanate, 50.8kg of defoaming agent DF-820, 18kg of flame retardant calcium sulfate inorganic fiber powder, 50kg of modified silicon nitride and 9100.04kg of wetting and dispersing agent Disponer;
[0115] The first polyether polyol is a difunctional polyether polyol with a molecular weight of 1000;
[0116] The silane-modified polyurethane polymer is obtained by capping a terminal isocyanate polymer having an NCO% content of 2.7% with a silane coupling agent, and specifically comprises the following steps:
[0117] Under stirring, the second polyether polyol is added to a reactor with nitrogen protection, the temperature is raised to above 120° C., vacuum dehydration is performed until the moisture content is less than 500 ppm, heating is stopped, the temperature is lowered to 45° C., the first polyisocyanate is added, heated to 80° C., and reacted for 3.5 hours, sampling is performed to detect NCO%, when the NCO% content is 5.4%, heating is stopped to obtain a terminal isocyanate polymer, the temperature is lowered to 45° C., a silane coupling agent is added, and the reaction is carried out for 1 hour. When the NCO% content is 2.7%, the temperature is lowered to 35° C. to stop the reaction, and a silane-modified polyurethane polymer is obtained;
[0118] The mass ratio of the second polyether polyol, the first polyisocyanate and the silane coupling agent is 100:43.8:27.4;
[0119] The second polyether polyol is a difunctional polyether polyol with a molecular weight of 1200;
[0120] The first polyisocyanate is MDI-50;
[0121] The silane coupling agent is obtained by mixing Dynasylan 1146 and VOK-225 in a mass ratio of 1:1.
[0122] Example 9
[0123] An environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries is obtained by mixing component A and component B in a volume ratio of 1:1; the component A is composed of the following raw materials: 10kg of a first polyether polyol, 8kg of bisphenol A modified polyether polyol HMP-604B, 8kg of modified castor oil SY770, 0.5kg of a chain extender propylene glycol, 0.5kg of a chain extender ethylene glycol, 0.5kg of a defoamer Defom68000, 0.5kg of a defoamer DF-8205, 7kg of zinc borate, 8kg of triphenyl phosphate, 60kg of modified silicon nitride, 1.5kg of an antioxidant Irganox1135, 0.5kg of SONOX168, 0.6kg of dibutyltin dilaurate, 0.4kg of pentamethyldiethylenetriamine, 0.005kg of a wetting and dispersing agent DISPERBYK-145, and 0.05kg of a wetting and dispersing agent Disponer 9100.005kg; the B component is composed of the following raw materials: 22kg of silane-modified polyurethane polymer, 25kg of methylene benzene diisocyanate, 2kg of dewatering agent toluenesulfonyl isocyanate, 51kg of defoamer DF-820, 0.8kg of defoamer DF-879D, 10kg of zinc borate, 15kg of triphenyl phosphate, 55kg of modified silicon nitride, 9100.03kg of wetting and dispersing agent Disponer, and 100.01kg of wetting and dispersing agent HY50;
[0124] The first polyether polyol is a difunctional polyether polyol with a molecular weight of 1500;
[0125] The silane-modified polyurethane polymer is obtained by capping a terminal isocyanate polymer having an NCO% content of 3.5% with a silane coupling agent, and specifically comprises the following steps:
[0126] Under stirring, adding the second polyether polyol to a reactor protected by nitrogen, heating to above 120° C., vacuum dehydrating to a water content of less than 500 ppm, stopping heating, cooling to 48° C., adding the first polyisocyanate, heating to 80° C., reacting for 4 hours, sampling to detect NCO%, when the NCO% content is 7.4%, stopping heating to obtain a terminal isocyanate polymer, cooling to 45° C., adding a silane coupling agent to react for 1.2 hours, cooling to 25° C. to stop the reaction when the NCO% content is 3.7%, and obtaining a silane-modified polyurethane polymer;
[0127] The mass ratio of the second polyether polyol, the first polyisocyanate and the silane coupling agent is 100:57.2:35.1;
[0128] The second polyether polyol is a difunctional polyether polyol with a molecular weight of 800;
[0129] The first polyisocyanate is obtained by mixing MDI-50 and dimethylbenzene diisocyanate in a mass ratio of 1:1;
[0130] The silane coupling agent is obtained by mixing Dynasylan 1146 and VOK-Y-15744 in a mass ratio of 1:2.
[0131] Example 10
[0132] An environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries is obtained by mixing component A and component B in a volume ratio of 1:1; the component A is composed of the following raw materials: 12 kg of a first polyether polyol, 12 kg of bisphenol A modified polyether polyol ST-280, 26 kg of modified castor oil HY-100, 3 kg of chain extender dipropylene glycol, 0.5 kg of defoamer DF-8205, and 0.5 kg of defoamer DF-879D 0.5kg, flame retardant calcium sulfate inorganic fiber powder 6kg, zinc borate 4kg, modified silicon nitride 45kg, antioxidant SONOX1682kg, antioxidant SONOX10761kg, dimorpholine diethyl ether 1.2kg, wetting dispersant Disponer9100.004kg and wetting dispersant HY50100.004kg; the B component is composed of the following raw materials: silane modified polyurethane polymer 20kg, dicyclohexylmethane diisocyanate 12kg, dewatering agent p-toluenesulfonyl isocyanate 1.5kg, defoamer DF-82050.5kg, defoamer DF-879D 0.7kg, flame retardant calcium sulfate inorganic fiber powder 15kg, modified silicon nitride 60kg, wetting dispersant Disponer 9100.03kg and wetting dispersant HY50100.01kg;
[0133] The first polyether polyol is a difunctional polyether polyol with a molecular weight of 1800;
[0134] The silane-modified polyurethane polymer is obtained by capping a terminal isocyanate polymer having an NCO% content of 2.4% with a silane coupling agent, and specifically comprises the following steps:
[0135] Under stirring, adding the second polyether polyol to a reactor protected by nitrogen, heating to above 120° C., vacuum dehydrating to a water content of less than 500 ppm, stopping heating, cooling to 46° C., adding the first polyisocyanate, heating to 78° C., reacting for 4 hours, sampling to detect NCO%, when the NCO% content is 4.7%, stopping heating to obtain a terminal isocyanate polymer, cooling to 45° C., adding a silane coupling agent to react for 1.2 hours, and cooling to 25° C. to stop the reaction when the NCO% content is 2.4%, to obtain a silane-modified polyurethane polymer;
[0136] The mass ratio of the second polyether polyol, the first polyisocyanate and the silane coupling agent is 100:30.4:78.9;
[0137] The second polyether polyol is a difunctional polyether polyol with a molecular weight of 1500;
[0138] The first polyisocyanate is obtained by mixing MDI-50 and dimethylbenzene diisocyanate in a mass ratio of 1:1;
[0139] The silane coupling agent is obtained by mixing VOK-225 and Dynasylan 1146 in a mass ratio of 1:3.
[0140] Embodiment 11
[0141] The method for preparing the environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium battery described in Example 5 comprises the following steps:
[0142] ① Preparation of component A: 7 kg of the first polyether polyol, 1 kg of bisphenol A modified polyether polyol HP-2000, 1 kg of modified castor oil SY770, 0.5 kg of chain extender propylene glycol, 8 kg of flame retardant calcium sulfate inorganic fiber powder and 30 kg of modified silicon nitride were added to a reactor with nitrogen protection, heated to 120° C. under stirring, vacuum dried and dehydrated for 1.5 h, cooled to 30° C., defoamer Defom 68000 0.2 kg, antioxidant Irganox 1135 0.2 kg, wetting dispersant DISPERBYK-145 0.003 kg and catalyst dibutyltin dilaurate 0.05 kg were added thereto, mixed for 30 minutes and then discharged to obtain component A;
[0143] ② Preparation of component B: 5 kg of silane-modified polyurethane polymer, 7 kg of diphenylmethane diisocyanate, 8 kg of flame retardant zinc borate, 30 kg of modified silicon nitride, 0.5 kg of dehydrating agent p-toluenesulfonyl isocyanate, 0.2 kg of defoaming agent BYK-A535 and 3 kg of wetting and dispersing agent Disponer 9100 were stirred and mixed for 30 minutes, and the mixture was discharged to obtain component B;
[0144] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a volume ratio of 1:1 to obtain an environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries.
[0145] Example 12
[0146] The method for preparing the environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium battery described in Example 6 comprises the following steps:
[0147] ① Preparation of component A: 25 kg of the first polyether polyol, 15 kg of bisphenol A modified polyether polyol HP-2280, 210 kg of modified castor oil HY-100, 3.5 kg of chain extender dipropylene glycol, 30 kg of flame retardant zinc borate, and 75 kg of modified silicon nitride were added to a reactor protected by nitrogen, heated to 130° C. under stirring, vacuum dried and dehydrated for 2.5 h, cooled to 40° C., and 52 kg of defoamer BYK-A53, 2.5 kg of antioxidant SONOX168, 0.05 kg of wetting and dispersing agent Disponer 910, and 1.5 kg of catalyst pentamethyldiethylenetriamine were added thereto, mixed for 40 minutes, and then discharged to obtain component A;
[0148] ② Preparation of component B: 25 kg of silane-modified polyurethane polymer, 35 kg of Suprasec 2020, 30 kg of flame retardant triphenyl phosphate, 70 kg of modified silicon nitride, 2.5 kg of dehydrating agent p-toluenesulfonyl isocyanate, 52 kg of defoaming agent DF-820 and 0.05 kg of wetting and dispersing agent HY5010 were stirred and mixed for 40 minutes, and the mixture was discharged to obtain component B;
[0149] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a volume ratio of 1:1 to obtain an environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries.
[0150] Embodiment 13
[0151] The method for preparing the environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium battery described in Example 7 comprises the following steps:
[0152] ① Preparation of component A: 10 kg of the first polyether polyol, 4 kg of bisphenol A modified polyether polyol HMP-604B, 2 kg of modified castor oil X150, 1 kg of chain extender 1,4-butanediol, 10 kg of flame retardant triphenyl phosphate, and 45 kg of modified silicon nitride were added to a reactor with nitrogen protection, heated to 122° C. under stirring, vacuum dried and dehydrated for 2 h, cooled to 32° C., defoamer DF-8205 0.5 kg, antioxidant Irganox B215 1 kg, wetting dispersant DISPERBYK-145 0.01 kg and catalyst dimorpholine diethyl ether 0.1 kg were added thereto, mixed for 38 minutes and then discharged to obtain component A;
[0153] ② Preparation of component B: 8 kg of silane-modified polyurethane polymer, 10 kg of methylene benzene diisocyanate, 10 kg of flame retardant triphenyl phosphate, 35 kg of modified silicon nitride, 1 kg of dehydrating agent p-toluenesulfonyl isocyanate, 0.8 kg of defoaming agent DF-8205 and 0.02 kg of wetting and dispersing agent DISPERBYK-145 were stirred and mixed for 32 minutes, and the mixture was discharged to obtain component B;
[0154] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a volume ratio of 1:1 to obtain an environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries.
[0155] Embodiment 14
[0156] The method for preparing the environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium battery described in Example 8 comprises the following steps:
[0157] ① Preparation of component A: 15 kg of the first polyether polyol, 7 kg of bisphenol A modified polyether polyol HMP-604B, 4 kg of modified castor oil SY770, 1.5 kg of chain extender ethylene glycol, 18 kg of flame retardant calcium sulfate inorganic fiber powder, and 45 kg of modified silicon nitride were added to a reactor with nitrogen protection, heated to 124 ° C under stirring, vacuum dried and dehydrated for 2 hours, cooled to 35 ° C, and added thereto 1.5 kg of defoamer DF-8205, 1.8 kg of antioxidant SONOX1076, 0.04 kg of wetting dispersant Disponer910 and 1 kg of catalyst triethylenediamine, mixed for 35 minutes and then discharged to obtain component A;
[0158] ② Preparation of component B: 15 kg of silane-modified polyurethane polymer, 25 kg of MDI-50, 18 kg of flame retardant calcium sulfate inorganic fiber powder, 1.8 kg of dehydrating agent p-toluenesulfonyl isocyanate, 0.8 kg of defoaming agent DF-8205, 0.04 kg of wetting and dispersing agent Disponer 910 and 50 kg of modified silicon nitride were stirred and mixed for 35 minutes, and the mixture was discharged to obtain component B;
[0159] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a volume ratio of 1:1 to obtain an environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries.
[0160] Embodiment 15
[0161] The method for preparing the environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium battery described in Example 9 comprises the following steps:
[0162] ① Preparation of component A: 10 kg of the first polyether polyol, 8 kg of bisphenol A modified polyether polyol HMP-604B, 8 kg of modified castor oil SY770, 0.5 kg of chain extender propylene glycol, 0.5 kg of chain extender ethylene glycol, 7 kg of zinc borate, 8 kg of triphenyl phosphate, and 60 kg of modified silicon nitride were added to a reactor protected by nitrogen, heated to 130 ° C under stirring, vacuum dried and dehydrated for 1.5 hours, cooled to 30 ° C, and defoamer Defom 68000 0.5 kg, defoamer DF-8205 0.5 kg, antioxidant Irganox 1135 1.5 kg, SONOX 168 0.5 kg, wetting dispersant DISPERBYK-145 0.005 kg, wetting dispersant Disponer 9100.005 kg, 0.6 kg of dibutyltin dilaurate and 0.4 kg of pentamethyldiethylenetriamine were mixed for 36 minutes and then discharged to obtain component A;
[0163] ② Preparation of component B: 22kg of silane-modified polyurethane polymer, 25kg of methylene benzene diisocyanate, 10kg of zinc borate, 15kg of triphenyl phosphate, 55kg of modified silicon nitride, 2kg of dewatering agent p-toluenesulfonyl isocyanate, 51kg of defoamer DF-820, 0.8kg of defoamer DF-879D, 0.03kg of wetting and dispersing agent Disponer 910, and 0.01kg of wetting and dispersing agent HY5010 were stirred and mixed for 36 minutes, and the mixture was discharged to obtain component B;
[0164] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a volume ratio of 1:1 to obtain an environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries.
[0165] Example 16
[0166] The method for preparing the environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium battery described in Example 10 comprises the following steps:
[0167] ① Preparation of component A: 12 kg of the first polyether polyol, 12 kg of bisphenol A modified polyether polyol ST-280, 26 kg of modified castor oil HY-100, 3 kg of chain extender dipropylene glycol, 6 kg of flame retardant calcium sulfate inorganic fiber powder, 4 kg of zinc borate and 45 kg of modified silicon nitride were added to a reactor with nitrogen protection, heated to 128 ° C under stirring, vacuum dried and dehydrated for 1.8 hours, cooled to 30-40 ° C, defoamer DF-8205 0.5 kg, defoamer DF-879D 0.5 kg, antioxidant SONOX16 82 kg, antioxidant SONOX10 7 61 kg, wetting dispersant Disponer 9100.004 kg and wetting dispersant HY50100.004 kg and dimorpholine diethyl ether 1.2 kg were added thereto, mixed for 35 minutes and then discharged to obtain component A;
[0168] ② Preparation of component B: 20 kg of silane-modified polyurethane polymer, 12 kg of dicyclohexylmethane diisocyanate, 15 kg of flame retardant calcium sulfate inorganic fiber powder, 60 kg of modified silicon nitride, 1.5 kg of dewatering agent p-toluenesulfonyl isocyanate, 0.5 kg of defoamer DF-8205, 0.7 kg of defoamer DF-879D, 0.03 kg of wetting and dispersing agent Disponer 910 and 0.01 kg of wetting and dispersing agent HY5010 were stirred and mixed for 35 minutes, and the mixture was discharged to obtain component B;
[0169] The silane-modified polyurethane polymer is an isocyanate-terminated polymer terminated by a silane coupling agent, and the silane coupling agent is one or two of Dynasylan 1146, VOK-225, and VOK-Y-15744;
[0170] ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a volume ratio of 1:1 to obtain an environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries.
[0171] The environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries obtained in Examples 11 to 16 was tested for performance, and the results are shown in Table 4.
[0172] The thermal conductivity is carried out in accordance with ASTM D5470-2017 Standard Test Method for Thermal Transfer Properties of Thermally Conductive Electrical Insulating Materials, the Shore D hardness is carried out in accordance with GB / T531.1-2008 Test Method for Indentation Hardness of Vulcanized Rubber or Thermoplastic Rubber Part 1: Shore Hardness Method (Shore Hardness) Method, the flame retardancy is carried out in accordance with GB / T2408-2008 Horizontal and Vertical Methods for Determination of Combustion Performance of Plastics, the dielectric strength is carried out in accordance with GB / T1408.1-2016 Electric Strength Test Method for Solid Insulating Materials, the volume resistivity is carried out in accordance with GB / T1410-2006 Volume Resistivity and Surface Resistivity Test Method for Solid Insulating Materials, the tensile strength and elongation at break are carried out in accordance with GB / T528-2009 Determination Method for Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber, and the shear strength is carried out in accordance with GB / T7124-2008 Determination of Tensile Shear Strength of Adhesives (Rigid Material to Rigid Material).
[0173] The shear strength and tensile strength, 85℃, 85%RH humidity and heat aging test and hot and cold alternating test processes are as follows: 85℃, 85%RH humidity and heat aging test: the test piece is kept in an environment of 85℃±2℃, 85%±5%RH for 1000 hours, then taken out, and then restored at room temperature for 2 hours for testing; Hot and cold alternating performance aging test: the highest temperature is 85±2℃, the lowest temperature is -40±2℃, each temperature is maintained for 1h, the temperature conversion time is less than 30min, 500 cycles are performed, and then restored at room temperature for 2h for testing.
[0174] Table 4 Performance test results
[0175]
[0176]
[0177] It can be seen from the results in Table 4 that the environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries of the present invention, the modified silicon nitride, the flame retardant are well compatible with other components, the structural adhesive has moderate hardness, good mechanical properties, and the change rate of mechanical properties after aging resistance test is good.
[0178] The present invention adopts bisphenol A modified polyether polyol, silane modified polyurethane polymer and polyisocyanate as the base material of the structural adhesive. On the one hand, the polyether polyol is compounded with bisphenol A modified polyether polyol and modified castor oil in component A, and the polyether polyol can provide excellent flexibility for the system; the benzene ring and carbon oxygen chain structure in the bisphenol A modified polyether polyol molecule can give the structural adhesive specific rigidity and toughness, and because of the high molecular cohesive energy, it has good high temperature resistance and hydrolysis resistance, can significantly improve cohesion and enhance bonding strength, so the prepared adhesive has good bonding performance and excellent moisture and heat resistance.
[0179] On the other hand, the synthesized terminal isocyanate polymer is partially capped with a silane coupling agent oligomer to obtain a silane-modified polyurethane polymer, which contains a certain amount of -NCO groups and is used in combination with monomeric isocyanates in component B. The siloxane structure in the modified polymer can react with the hydroxyl groups on the substrate, which can enhance the adhesion of the structural adhesive on the substrate surface and effectively improve the adhesion of the adhesive product; the Si-O-Si cross-linked network layer in the silane coupling agent oligomer structure can effectively prevent water molecules from penetrating, has excellent hydrophobicity, can effectively reduce the water absorption rate of the adhesive product, and enhance the water resistance and moisture resistance of the adhesive product; and because the modified polymer has good hydrophobicity, the system does not add conventional hydrophobic agents, and can also have good storage stability.
Claims
1. An environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries, characterized in that: The environmentally friendly polyurethane thermally conductive structural adhesive for energy storage lithium batteries uses modified silicon nitride as a thermally conductive filler; The modified silicon nitride is prepared according to the following steps: Add silicon nitride to a potassium hydroxide aqueous solution, heat to 115-125°C for reaction for 40-50 hours under stirring, cool to 20-30°C, filter, wash with deionized water until the pH value of the filtrate is 7-8, and vacuum dry the filtered powder to obtain Si3N4-OH powder; Add Si3N4-OH powder to silane coupling agent KH560-ethanol solution, stir and mix for 2 to 4 hours, centrifuge, wash the solid powder with ethanol, and vacuum dry to obtain modified silicon nitride; The mass ratio of silicon nitride, potassium hydroxide aqueous solution, and silane coupling agent KH560-ethanol solution is 1:3-4:3-4; The mass concentration of the potassium hydroxide aqueous solution is 3-7 mol / L; The mass concentration of the silane coupling agent KH560-ethanol solution is 0.8-1.2%.
2. The environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries according to claim 1, characterized in that: The environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium battery is obtained by mixing component A and component B in a volume ratio of 1:1; the component A is composed of the following raw materials in parts by weight: 7-25 parts of a first polyether polyol, 1-15 parts of bisphenol A modified polyether polyol, 1-10 parts of modified castor oil, 0.5-3.5 parts of a chain extender, 0.2-2 parts of a first defoamer, 8-30 parts of a first flame retardant, 30-75 parts of modified silicon nitride, 0. 2-2.5 parts, 0.05-1.5 parts of catalyst and 0.003-0.05 parts of first wetting and dispersing agent; the B component is composed of the following raw materials in parts by weight: 5-25 parts of silane-modified polyurethane polymer, 7-35 parts of second polyisocyanate, 0.5-2.5 parts of dewatering agent, 0.2-2 parts of second defoaming agent, 8-30 parts of second flame retardant, 30-70 parts of modified silicon nitride and 0.003-0.05 parts of second wetting and dispersing agent; The first polyether polyol is a difunctional polyether polyol having a molecular weight of 400 to 2000; The silane-modified polyurethane polymer is an isocyanate-terminated polymer terminated by a silane coupling agent, and the silane coupling agent is one or two of Dynasylan 1146, VOK-225, and VOK-Y-15744.
3. The environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries according to claim 2, characterized in that: The silane-modified polyurethane polymer is obtained according to the following steps: Under stirring, adding the second polyether polyol to a reactor with nitrogen protection, heating to above 120° C., vacuum dehydrating to a water content of less than 500 ppm, stopping heating, cooling to 40-50° C., adding the first polyisocyanate, heating to 75-83° C., reacting for 3-4.5 hours, sampling to detect NCO%, when the NCO% content is 3.7-8.5%, stopping heating to obtain a terminal isocyanate polymer, cooling to 40-50° C., adding a silane coupling agent to react for 1-1.5 hours, cooling to 20-30° C. to stop the reaction, and obtaining a silane-modified polyurethane polymer; The mass ratio of the second polyether polyol, the first polyisocyanate and the silane coupling agent is 100:26.3-78.0:10.2-61.5; The second polyether polyol is a difunctional polyether polyol having a molecular weight of 700 to 2000; The first polyisocyanate is one or two of L-lysine diisocyanate, MDI-50, dimethylenebenzene diisocyanate, and diphenylmethane diisocyanate; The silane coupling agent is one or two of Dynasylan 1146, VOK-225 and VOK-Y-15744.
4. The environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries according to claim 3, characterized in that: A silane coupling agent is added to react for 1 to 1.5 hours. When the NCO% content is 1.8 to 4.3%, the temperature is lowered to 20 to 30° C. to stop the reaction and obtain a silane-modified polyurethane polymer.
5. The environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries according to any one of claims 2 to 4, characterized in that: The bisphenol A modified polyether polyol is one or two of HP-2000, HP-2280, HMP-604B, and ST-280; The modified castor oil is one or two of SY770, HY-1002 and X150; The first defoamer and the second defoamer are one or two of Defom 6800, BYK-A535, DF-8205, and DF-879D; The first flame retardant and the second flame retardant are one or two of calcium sulfate inorganic fiber powder, zinc borate, and triphenyl phosphate; The antioxidant is one or two of Irganox1135, SONOX168, SONOX1076, and Irganox B215; The first wetting and dispersing agent and the second wetting and dispersing agent are one or two of DISPERBYK-145, Disponer 910, and HY5010; The second polyisocyanate is one or two of modified isocyanate MDI, liquefied MDI, MDI-50, dimethylbenzene diisocyanate, and dicyclohexylmethane diisocyanate; The dewatering agent is p-toluenesulfonyl isocyanate.
6. The environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries according to any one of claims 2 to 4, characterized in that: The chain extender is one or two of propylene glycol, dipropylene glycol, 1,4-butanediol and ethylene glycol.
7. The environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries according to any one of claims 2 to 4, characterized in that: The catalyst is one or two of dibutyltin dilaurate, pentamethyldiethylenetriamine, dimorpholine diethyl ether and triethylenediamine.
8. The method for preparing any one of the environmentally friendly polyurethane thermal conductive structural adhesives for energy storage lithium batteries according to claims 2 to 7, characterized in that: The following steps are involved: ① Preparation of component A: by weight, add 7-25 parts of the first polyether polyol, 1-15 parts of bisphenol A modified polyether polyol, 1-10 parts of modified castor oil, 0.5-3.5 parts of chain extender, 8-30 parts of the first flame retardant, and 30-75 parts of modified silicon nitride into a reactor with nitrogen protection, heat to 120-130° C. under stirring, vacuum dry and dehydrate for 1.5-2.5 hours, cool to 30-40° C., add 0.2-2 parts of the first defoamer, 0.2-2.5 parts of the antioxidant, 0.003-0.05 parts of the first wetting and dispersing agent, and 0.05-1.5 parts of the catalyst, mix for 30-40 minutes, and then discharge to obtain component A; The first polyether polyol is a difunctional polyether polyol having a molecular weight of 400 to 2000; ② Preparation of component B: 5-25 parts of silane-modified polyurethane polymer, 7-35 parts of the second polyisocyanate, 8-30 parts of the second flame retardant, 30-70 parts of modified silicon nitride, 0.5-2.5 parts of dewatering agent, 0.2-2 parts of the second defoaming agent and 0.003-0.05 parts of the second wetting and dispersing agent were stirred and mixed for 30-40 minutes, and the mixture was discharged to obtain component B; The silane-modified polyurethane polymer is an isocyanate-terminated polymer terminated by a silane coupling agent, and the silane coupling agent is one or two of Dynasylan 1146, VOK-225, and VOK-Y-15744; ③ When in use, the component A obtained in step ① and the component B obtained in step ② are evenly mixed in a volume ratio of 1:1 to obtain an environmentally friendly polyurethane thermal conductive structural adhesive for energy storage lithium batteries.